Biochar da casca de Eucalyptus para aplicação agroflorestal - Pires, Ariane Aparecida Felix (Universidade Federal de São Carlos, 2024)
Lately, the interest in biochar has grown, driving research in Brazil and abroad on its application in soils, as an adsorbent, and for carbon sequestration. Plant biomass, abundant on Earth, is the main material studied to produce this product obtained by the action of heating under O2 limited conditions. In Brazil, there is research potential due to the extensive agroforestry areas cultivated, which generate large amounts of waste during harvesting and processing. A sustainable approach was focused and associated with the added value in the reuse of environmental liability of the timber sector. Eucalyptus bark was the raw material in this study to produce biochar with the purpose of conditioning the soil, to provide carbon, minerals and promote pH control. The characterization of the material was carried out to know its properties and the pyrolysis conditions were defined. Four treatments were tested, varying the temperature (300 °C, 350 °C, 400 °C and 450 °C) with residence time set at 2 hours. The results of the proximate analysis and yield indicated that fixed carbon and gravimetric yield are inversely proportional. The results of X-ray diffraction (X-DR) analysis, Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA) complemented each other and confirmed the changes undergone by the Eucalyptus bark during the thermochemical conversion process. Dynamic and isothermal thermogravimetric tests were carried out in an inert atmosphere, simulating the parameters used in a muffle furnace for a larger production scale. The temperature of the maximum rate of degradation (Tmax) of Eucalyptus bark, 380 °C, was determined in the DTG curve of the dynamic test and verified in the TG curve of the isothermal test. The treatment at 450 °C stood out for its high fixed carbon content, elevated pH, lower volatile content, and greater thermal stability due to its amorphous and aromatized structure.
Eucalyptus bark biochar for agroforestry application
Keywords: Pirólise; Carbono fixo; Degradação térmica; Estabilidade térmica; Pyrolysis; Fixed carbon; Thermal degradation; Thermal stability; CIENCIAS EXATAS E DA TERRA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL